Assessment of molecular diversity among Pearl Millet (Pennisetum glaucum (L.) R. Br.) Maintainer (B) and Restorer (R) lines. : Molecular diversity in pearl millet - Tomar, Rukam Singh (Annals of Arid Zone, 2023)
Pearl millet is predominantly cultivated in western arid and semi-arid region. Pearl millet productivity has drastically increased in the seven decades mainly due to adoption of hybrid varieties in large. Hybrid development programme mainly depends upon exploitation of diverse genetic stock. In the present study a set of 48 maintainer line (B) and 52 restorer ® parent were assessed for molecular diversity using PCR based RAPD and ISSR markers. The Jaccard’s similarity coefficient was used to create pair-wise comparisons of distinct and shared polymorphic amplification products. The dendrogram represented the classification of all 100-pearl millet genotypes into two major groups. First group was formed with single genotype J-2296 and second group consisted of 99 genotypes further grouped in three sub-clusters. In second major cluster, maximum genotypes were grouped in subcluster I (45) followed by subcluster II (35) and subcluster III (19). Grouping of B lines and R lines were random no specific grouping was observed. The observed divergence can be useful for selecting B lines and R lines from different clusters for developing hybrids. J-2296 seems to be highly diverse from rest of the genotypes, it can be used for hybrid development as well as for R line improvement.